Perlindungan Hak Asasi Manusia bagi Pihak Ketiga dalam Perampasan Aset Berbasis Non-Pidato: Perbandingan Indonesia dan Australia - Andini, Orin Gusta; Boer, Muhammad Riyan Kchfoi; Tanjung, Sisi A.; Odelia, Marsha (Faculty of Law, Universitas Jambi, 2025)
Background: The ever-evolving international legal framework prioritizes the enforcement and protection of human rights and global justice. States are encouraged to underline their obligations in preventing human rights violations, particularly in law enforcement practices. Indonesia, although it has ratified the UNCAC, has still not ratified the mechanism for the confiscation of assets resulting from corruption crimes without the need for a conviction or as well known as the Non-Conviction-based Asset Recovery (NCB). The relationship between the NCB and human rights is the source of the problem of law enforcement to eradicate corruption in Indonesia. Therefore, this article explains the protection of human rights, especially those concerning the third-party, in the asset forfeiture bill in Indonesia and compares it with the implementation of the NCB in Australia. Methodology: Using a legislative approach to examine the legal provisions applicable in both countries, namely Indonesia and Australia, this paper relies on the study of relevant legal sources, including anti-corruption law and human rights law. Objective: This study is expected to provide an overview of the human rights protection mechanism in the enforcement of the law on the confiscation of assets resulting from corruption without the need to go through the criminal process first in Indonesia. Findings: The study found that the draft asset forfeiture law in Indonesia does not offer balanced legal protection for third party human rights, specifically the right to own property acquired in good faith or without criminal involvement. Indonesia is advised to adopt a mechanism for asset forfeiture without criminal proceedings as implemented in Australia, which guarantees asset ownership rights for bona fide the third-party to reformulate human rights in the bill. Originality/Uniqueness: This research is relevant and necessary in the development of the concept of multinational asset recovery in Indonesia by prioritizing the balance of human rights protection, especially for the third-party.